Intelligent Biometric Detection System for Disabled People - Gede Pramudya, A.; Muda, A. K. (2011)
This paper presents an intelligent system for disabled people to have a full control of computers using biometric detection so that they can still operate computers like normal people do. An idea behind this project is a fact that the emergence of difficulties for disabled people to interact with computers. For instance, paralyzed people are unable to control computer mouse. Hence this project was conducted. This project only uses a webcam as an input which captures the user’s head and then tracks their head movement and iris in order to control the mouse actions. It is done by using image processing techniques such as Component Localization, Haar Cascade classifier and Hough transform.